Efektivitas Penerapan Pembelajaran Daring Terhadap Tingkat Pemahaman Belajar Mahasiswa Dimasa Pandemi Covid-19 - Endang Suryana; Dedeh Supriyanti; Fadhillah Nur Widjajanti (UNIVERSITAS RAHARJA, 2021)
Since March 2020, online learning has been implemented, especially in universities in Indonesia as a result of the Covid-19 pandemic. And in its implementation some obstacles also occur, so that it is possible to also have an impact on students' understanding of the teaching materials delivered. Therefore, the purpose of this research is to help determine the effectiveness of online learning systems that have been implemented. The research was conducted using qualitative method by distributing questionnaires through social media and has been responded by 197 students both from State Universities and Private Universities. Then the data were analyzed using Miles and Huberman analysis techniques that resulted in the online learning system being implemented effectively enough so that students could understand the teaching materials that had been delivered with the condition of many students doing online learning at home using laptops or computers and personal data packages with moderate signal conditions.